Protein intake and risk of frailty among older women in the Nurses' Health Study. Issue 3 (23rd March 2022) - Struijk, Ellen A.; Fung, Teresa T.; Rodríguez‐Artalejo, Fernando; Bischoff‐Ferrari, Heike A.; Hu, Frank B.; Willett, Walter C.; Lopez‐Garcia, Esther
Abstract: Background: There is evidence that an overall healthy diet is associated with lower risk of frailty. However, the effect of diet composition, specifically the role of protein intake on frailty, is mostly unclear. The aim of this study was to evaluate the intake of protein, including total, plant, animal, and dairy protein, in relation to frailty incidence in a large cohort of older women. Methods: We analysed data from 85 871 women aged ≥60 participating in the Nurses' Health Study. Intake of protein was measured nine times during follow‐up from 1980 until 2010. Frailty was defined as having at least three of the following five criteria from the Fatigue, Resistance, Ambulation, Illnesses and Loss of Weight (FRAIL) scale: fatigue, low strength, reduced aerobic capacity, having ≥5 illnesses, and weight loss of ≥5%. The occurrence of frailty was assessed every 4 years from 1992 up to 2014. Results: During follow‐up, we identified 13 279 incident cases of frailty. Women with a higher intake of plant protein had a lower risk of developing frailty after adjustment for all relevant confounders [relative risks across quintiles of consumption: 1.00, 0.94, 0.89, 0.86, and 0.86; P ‐trend < 0.001]. In contrast, those with a higher intake of animal protein intake had a higher risk of frailty [relative risks across quintiles of consumption: 1.00, 0.98, 0.99, 1.00, and 1.07; P ‐trend 0.04]. The intake of total and dairy protein showed no significant association with frailty in the full model. Substituting 5% of energy from plant protein intake at the expense of animal protein, dairy protein, or non‐dairy animal protein was associated with 38% (29%, 47%), 32% (21%, 42%), and 42% (33%, 50%) reduced risk of frailty. Conclusions: A higher intake of plant protein, but not animal or dairy protein, was associated with a lower risk of frailty. Substitution of plant protein for animal protein, especially non‐dairy animal protein, was associated with lower risk of frailty.